Surviving the cold: a review of the effects of cold spells on bivalves and mitigation measures - Masanja, Fortunatus; Xu, Yang; Yang, Ke; Mkuye, Robert; Deng, Yuewen; Zhao, Liqiang (Frontiers in Marine Science, 2023)
Cold spells, characterized by prolonged periods of low temperature, have become increasingly frequent, intense, and prolonged due to the ongoing effects of climate change, resulting in devastating consequences for marine ecosystems and significant socio-economic impacts. As ectothermic organisms, bivalves are dependent on their environment for regulating body temperature, and thus, cold spells can disrupt their normal functioning, leading to mass mortalities. This review comprehensively summarizes the effects of cold spells on bivalves and proposes mitigation measures to be considered in future bivalve farming and management plans. Scientific evidence has indicated that cold spells can alter bivalve metabolism, leading to an increase in stress protein production and a decrease in the activity of energy metabolism-related enzymes, which can negatively impact the bivalve immune system and increase the risk of disease. To mitigate the effects of cold spells on bivalves, a number of strategies can be employed, including the use of thermal shelters such as floating covers, selective breeding of more cold-tolerant bivalves, and genetic engineering to enhance the expression of heat-shock proteins in bivalves. The impacts of cold spells on bivalves are significant, affecting both their physiological and molecular processes. Through the implementation of thermal shelters, selective breeding, and genetic engineering, the effects of cold spells on bivalves can be reduced, improving their survival and growth. Further research is required to fully understand cold spells’ impacts on bivalves and develop effective mitigation measures.